Women’s Voices and Patriarchal Hegemony of the Edo Period in Shinju Tenno Amijima (1720) - Nina Alia Ariefa (Universitas Diponegoro, 2021)
The Edo Period (1603-1868), known as the feudal era, lasted for nearly three centuries in Japan. Confucian teachings applied in all sectors of life had a great influence on the expansion of the patriarchal system in Japanese society at this time. Under the strict control of the Tokugawa shogunate government, the implementation of social class stratification was firmly established, including in the hierarchical relationship between men and women. The period of peace that occurred throughout the Edo period had contributed to a conducive situation for the rapid development of Japanese culture. Male artists were very dominant in the development of Japanese culture, and they were centred in big cities during this period. On the other hand, this era had become a dark age for women who did not get the opportunity to speak and create as men did. The female figures of the Edo period were presented in the works of male writers. This study focuses on examining women’s voices in the works of these male writers in the period. After exploring research on this period’s literary works, we found that these studies have various focuses related to the disclosure of women during the period, starting from the representation of women, their relationship with a male and other female characters, to their roles and positions. This research will contribute to discussions on gender, history, and literature, as well as on the way women's voices in this work serve a purpose in supporting the patriarchal hegemony that occurred in the period. We aim to reveal women’s voices in a male writer's play Shinju Tenno Amijima (1720) by Chikamatsu Monzaemon (1653-1725) through a feminist critique approach. To explain women's voice and patriarchal hegemony, we apply the concepts of silence from Olsen (2003) and hegemony from Antonio Gramsci. The results of this study indicate that women’s voices raised in this play are the ones who support men's interests and are subject to patriarchal values. This play consistently displays the exclusion of women's voices of opposition and defiance. This work also shows its existence as a locus for the dominant values emphasized for women in the Edo period.